Procedures adopted by orthodontists for space closure and anchorage control - Monini, André Da Costa [UNESP]; Gandini Júnior, Luiz Gonzaga [UNESP]; Santos-pinto, Ary Dos [UNESP]; Maia, Luiz Guilherme Martins [UNESP]; Rodrigues, Willian Caetano (Dental Press International, 2013)
OBJECTIVE: The aim of this study was to identify the procedures adopted by Brazilian orthodontists in the following situations: extraction space closure, anchorage control in case of necessary anchorage for group A and frequency of skeletal anchorage use, especially in the upper jaw. METHOD: A questionnaire was sent to the e-mail address of all dentists registered in the Brazilian Federal Council of Dentistry. RESULTS: The results showed that most Brazilian orthodontists usually perform extraction space closure by means of sliding mechanics. The use of palatal bar, inclusion of second molars in the archwire and space closure performed in two phases are the most used techniques for anchorage control in the upper jaw. The skeletal anchorage is referenced by 36.5% of specialists as a routine practice for the upper jaw anchorage. CONCLUSIONS: There is a wide variety of procedures adopted by Brazilian orthodontists for orthodontic space closure and anchorage control.

OBJETIVO: esse trabalho tem o objetivo de identificar as condutas adotadas pelos ortodontistas brasileiros para o fechamento ortodôntico de espaços de extrações, controle de ancoragem em caso de necessidade de ancoragem do grupo A, e frequência de uso de ancoragem esquelética nesses casos, especialmente na arcada superior. MÉTODOS: um questionário foi enviado para o endereço eletrônico de todos os ortodontistas inscritos no Conselho Federal de Odontologia. RESULTADOS: os resultados mostraram que a maioria dos ortodontistas brasileiros usualmente faz fechamento de espaço de extrações com mecânicas de deslizamento. O uso de barra palatina, incorporação de segundos molares no arco e fechamento de espaço em duas fases são as condutas mais utilizadas para controle de ancoragem na arcada superior. A ancoragem esquelética é referenciada por 36,5% dos especialistas como forma rotineira de ancoragem na arcada superior. CONCLUSÕES: existe uma grande variedade de condutas adotas por ortodontistas brasileiros tanto para o fechamento ortodôntico de espaço quanto para o controle de ancoragem em casos de maior necessidade de retração anterior.
Keywords: Procedimentos de ancoragem ortodôntica; Fechamento de espaço ortodôntico; Questionários; Orthodontic anchorage procedures; Orthodontic space closure; Questionnaires